Physical chemistry for the chemical sciences - Chang, Raymond (University Science Books, 2014)
This text has been extensively revised both in level and scope. Targeted to a mainstream physical chemistry course, this text features extensively revised chapters on quantum mechanics and spectroscopy, many new chapter-ending problems, and updated references, while biological topics have been largely relegated to the previous two textbooks. Other topics added include the law of corresponding states, the Joule-Thomson effect, the meaning of entropy, multiple equilibria and coupled reactions, and chemiluminescence and bioluminescence. One way to gauge the level of this new text is that students who have used it will be well prepared for their GRE exams in the subject. Careful pedagogy and clear writing throughout combine to make this an excellent choice for your physical chemistry course.